The Role of TESDA Short Courses and Diploma Programs in Equipping Learners with Skills for the Hospitality and Service Industry in the Three Branches of Holy Trinity School of Science and Technology Inc: Basis for an Enhanced Curriculum and Industry Partnership Plan - Tanaman, Rene (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the role of TESDA short courses and diploma programs in equipping learners with the competencies required for the hospitality and service industry in the three branches of Holy Trinity School of Science and Technology, Inc. Specifically, it examined the extent to which the programs developed learners’ technical competencies, customer service skills, ability to apply theoretical knowledge in practical settings, confidence in performing industry-related tasks, and readiness for employment or entrepreneurship. It also evaluated the effectiveness of the current curriculum in terms of alignment with TESDA competencies, integration of hands-on and experiential learning, inclusion of industry standards and best practices, support for collaborative and problem-solving activities, and learner satisfaction and perceived relevance of training. The study employed a quantitative descriptive research design using a validated structured questionnaire administered to learners and teachers selected through purposive sampling. Data were analyzed using frequency, percentage, weighted mean, composite mean, and Pearson Product-Moment Correlation. Findings revealed that respondents generally agreed that TESDA short courses and diploma programs effectively equipped learners with the competencies required in the hospitality and service industry. Likewise, the current curriculum was perceived to be effective in preparing learners for employment through competency-based instruction, practical training, and industry-relevant learning experiences. The study further identified opportunities for strengthening curriculum alignment with evolving TESDA standards, expanding industry partnerships, enhancing experiential learning opportunities, and promoting entrepreneurship. Based on the findings, an Enhanced Curriculum and Industry Partnership Plan was proposed to further improve learners’ employability, technical competence, and overall readiness for careers in the hospitality and service sector.